Morning call of siamang (Symphalangus syndactyllus) in Subayang River, Riau – Indonesia - Zulamri (International Journal of Ecophysiology, 2019)
Morning call in siamang is very important for the life of siamang. This behavior is important to mark its territory, communicate with neighboring groups, etc. The this research aims to determine the time of vocalization, the position of trees and the strata canopy used by gibbons in vocalization. This research was conducted in WWF Indonesia Central Sumatra Research Station Subayang Camp at Rimbang Baling Wildlife Reserve for 2 months from July until August 2017 using Visual Encounter Survey (VES) method. From this research we knew that morning call in siamang usually occurs from 08.00 am – 10.00 am in the morning. Siamang appears to choose emergent tree in the forest ridge or emergent tree on the hill slope to do vocalization. During vocalization, siamang tends to use the 3rd and the 4th strata or upper canopy layer and emergent layer which are higher than 20 m from the forest surface. This height facilitates the siamang to maximize transmission of the vocalization to the surrounding area and communicate with other groups.